ANALISIS MISKONSEPSI MAHASISWA PROGRAM STUDI PGSD UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR PADA MATERI MEKANIKA DENGANMENGGUNAKAN METODE CERTAINLY OF RESPONS INDEX(CRI) - ANDRIONO MANALU; MUKTAR PANJAITAN; ROITA MEILANI NAIBAHO (LP2MTBM MAKARIOZ, 2019)
This study aims to uncover the misconceptions of students of the Elementary School Teacher Education Study Program (PGSD) University of HKBP Nommensen Pematangsiantar on Mechanics Material in odd semester T.A 2018/2019 in the Science Concept Basic Subject Course I. The research method used in this study was a survey. The study population was 321 PGSD students who were divided into 8 groups and the sample used was 6 groups by means of sampling using a random sampling technique. The research instrument used in this study was a Multiple Choice Test accompanied by a CRI column. From the research it was found that the percentage of students who experienced misconceptions was 11.6% and the percentage was smaller than the percentage of students who did not understand the concept, the percentage of students who did not understand the concept was 17.8% and the percentage of students who understood the concept was 70.5% . Many students' misconceptions occur when the use of vectors in mechanics, the concept of variables that do not appear in general mechanics but appear in daily life such as the influence of mass when falling objects rub against air.